2019
DOI: 10.1111/ejn.14560
|View full text |Cite
|
Sign up to set email alerts
|

Nasal respiration entrains neocortical long‐range gamma coherence during wakefulness

Abstract: Recent studies have shown that slow cortical potentials in archi‐, paleo‐ and neocortex can phase‐lock with nasal respiration. In some of these areas, gamma activity (γ: 30–100 Hz) is also coupled to the animal's respiration. It has been hypothesized that these functional relationships play a role in coordinating distributed neural activity. In a similar way, inter‐cortical interactions at γ frequency have also been associated as a binding mechanism by which the brain generates temporary opportunities necessar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…In addition to these findings in humans, Bosman et al (2012) provided preliminary evidence from two macaque monkeys showing that V1-V4 coherence at 70-80 Hz depends on the time from the peaks of the 3-5 Hz-filtered LFP component. Furthermore, we have also recently shown that the phase of respiratory activity modulates low gamma synchrony in the awake cat (Cavelli et al, 2019). Altogether, the current and previous evidence suggests that the rhythmic modulation of phase synchrony may be a general brain mechanism preserved across species.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to these findings in humans, Bosman et al (2012) provided preliminary evidence from two macaque monkeys showing that V1-V4 coherence at 70-80 Hz depends on the time from the peaks of the 3-5 Hz-filtered LFP component. Furthermore, we have also recently shown that the phase of respiratory activity modulates low gamma synchrony in the awake cat (Cavelli et al, 2019). Altogether, the current and previous evidence suggests that the rhythmic modulation of phase synchrony may be a general brain mechanism preserved across species.…”
Section: Discussionsupporting
confidence: 71%
“…The respiratory rate was below 2 Hz (Fig. 1), similar to that in unanesthetized rats during sleep 7,34,35 , and remained stable over alternating theta and non-theta states (1.80±0.14 and 1.73±0.14 Hz, respectively; Table 1), resulting in a single sharp peak in the diaphragmal (dia) autospectra (Fig. 2A).…”
Section: Resultsmentioning
confidence: 54%
“…Lack of RRO under urethane was occasionally reported in previous studies, but only in deep anesthesia characterized by slow neocortical up-down transitions 36, 46 , i.e. a pattern similar to natural slow wave sleep, where however RRO remains absent after switching to theta-rich REM sleep 7,34,35 . Under urethane anesthesia, both OB-PFC and OB-HC coherences showed strong correlations with dia-OB coherence in both theta and non-theta states, again violating the correspondence, commonly expected on the basis of EEG signals, between urethane-theta and AW-REM on one hand and between urethane non-theta and QW-SWS on the other.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations